Regulation of crystal induced inflammation: current understandings and clinical implications. (3rd July 2021) - Galozzi, Paola; Bindoli, Sara; Luisetto, Roberto; Sfriso, Paolo; Ramonda, Roberta; Scanu, Anna; Oliviero, Francesca
ABSTRACT: Introduction : Accumulation of abnormal crystals in the body, derived from endogenous or exogenous materials can drive a wide spectrum of inﬂammatory disease states. It is well established that intra-articular deposition of monosodium urate (MSU) and calcium pyrophoshate (CPP) crystals contributes to joint destruction through pro-inflammatory processes. Areas covered : This review will focus on current understanding and recent novelty about the mechanisms and the clinical implications of the inflammation induced by MSU and CPP crystals. Expert opinion : Advances in molecular biology reveal that at the base of the inflammatory cascade, stimulated by MSU or CPP crystals, there are many complex cellular mechanisms mainly involving the NLRP3 inflammasome, the hallmark of autoinflammatory syndromes. The extensive studies carried out through in vitro and in vivo models along with a better clinical definition of the disease has led to an optimized use of existing drugs and the introduction of novel therapeutic strategies. In particular, the identification of IL-1 as the most important target in gout and pseudogout has made it possible to expand the pharmacological indications of anti-IL-1 biological drugs, opening new therapeutic perspectives for patients.